Selection of a rational method for hardening carbide cutting tools for heavy engineering - Kovalev, Viktor; Klymenko, Galyna; Vasylchenko, Yana; Shapovalov, Maksym; Manokhin, Andrey (Видавництво Львівської політехніки, 2023)
An important task is to improve cutting tools for high-precision productive machining of difficult-to-machine materials by applying the latest tool hardening methods. This is especially true for carbide-cutting tools. The paper analyzes the current state of the problem of improving the tooling of new machine tools for high-precision productive machining of hard-tomachine materials. The main known methods of increasing the wear resistance and strength of carbide tools can be divided into the following groups: structural methods; mechanical hardening; wearresistant coatings; chemical and thermal treatment; laser hardening; plasma-arc hardening; radiation hardening; ionic alloying; magnetic abrasive treatment; and pulsed magnetic field treatment. The choice of a particular hardening method depends on many factors that determine its effectiveness and costs in certain production conditions. The conditions for machining large-sized parts at heavy engineering enterprises are analyzed. It was found that, along with wear, the destruction of the cutting part in the form of pitting and fracture is significant. Statistical studies have proven that when machining on heavy machine tools, the cutting force allowed by the machine tool mechanisms does not limit the cutting modes. The maximumvalues of forces are up to 10 times higher than their average value, which is usually used to calculate the design parameters of cutting tools An analysis of various methods for improving the physical and mechanical properties of carbide tool materials has shown that the best combination of cost and production efficiency is observed in pulsed magnetic field treatment. The use of magnetic fields in cutting processes and tool hardening is a promising area of high-technology development in machining. Increasing tool life can be achieved by the influence of a magnetic field either on the conditions of the cutting process or on the structure and physical and mechanical properties of tool materials with ferromagnetic components.
Keywords: cutting tools; carbide tool materials; magnetic field; strength